Modulation of a7nAchR for cardioprotection against isoprenaline-induced myocardial injury - Chee, Hooi Chung; Mohammad Yusuf Hasan,; Satirah Zainalabidin,; Chua, Eng Wee; Azizah Ugusman,; Zakiah Jubri,; Mohd Kaisan Mahadi, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The α7nAchR gene is expressed in immune cells, including macrophages, and is linked to cardiovascular diseases. The cardioprotective effects of α7nAchR activation against inflammation in isoprenaline-induced myocardial injury are unclear. This study aims to assess the cardioprotective effects of α7nAChR activation on isoprenaline-induced myocardial injury rats. We hypothesized that α7nAChR activation provides cardioprotection against the myocardial injury via the cholinergic anti-inflammatory pathway. Isoprenaline hydrochloride (85 mg/kg) was injected subcutaneously in rats to induce myocardial injury and activated the a7nAchR through daily transcutaneous tragus stimulation for 14 days at 20 Hz, 0.2 ms, and 2 mA. Examination on Langendorff isolated heart perfusion technique showed improvement in cardiac functions. The electrical stimulation affected collagen deposition, circulating troponin T, and circulating inflammatory marker TNFα. The effects were abolished with pharmacological inhibition of α7nAChR. Further, the role of α7nAChR in ischemia-induced inflammation was studied in RAW264.7 macrophages. Inflammation was activated in RAW264.7 macrophages that were treated with glucose-free media, flushed with 95% N2, and 5% CO2 for 1 h, and reoxygenated in a normoxic incubator for 24 h. a7nAchR stimulation in the activated macrophages reduced pro-inflammatory markers (NO, TNFα) but did not affect anti-inflammatory (IL10, TGFb) expression levels. The reduction in pro-inflammatory factors was linked to the modulation of the transcriptional regulator NFκB, but not STAT3. Our findings suggest that activation of the cholinergic anti-inflammatory pathway may protect against isoprenaline-induced cardiac injury by improving cardiac performance and regulating inflammatory macrophage activity potentially via the NFκB/TNFα pathway.